Optimal robust sizing of distributed energy storage considering power quality management - Ying Zhu; Juan Wei; Bozhong Wang; Shiyu Hong; Yutong Liu; Liang Lu (IET Renewable Power Generation)
Abstract This paper proposes an optimal robust sizing model for distributed energy storage systems (DESSs) considering power quality management. The power conversion systems (PCSs) of DESSs with four‐quadrant operation characteristics can provide power quality management services to customers. To improve capacity utilization of the DESS, power quality management services are quantified and integrated into an optimal bi‐level sizing model, where the upper level addresses the sizing problem concerning battery and PCS capacities, while the lower level focuses on coordinating active/reactive power control of the DESS. A robust optimization approach for DESS scheduling is adopted to consider uncertainties of distributed photovoltaic (PV) power generation and power quality management requirements. The column and constraint generation (C&CG) algorithm is applied for efficient handling of this model. Ultimately, the effectiveness of the proposed approach is validated through comprehensive comparative analysis of four cases, resulting in a 12.44% increase in the net present value (NPV) over the entire lifecycle.